ECONOMIC COOPERATION OF THE BUKHARA PUBLIC SOVIET REPUBLIC (BPSR) WITH ITALY - Nuridinov Turdali Kambarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The following article explains BPSR`s cooperation with Italy. Trade representation in Bukhara`s Caucasus opens economic relations with Italian “Benedict LTD” and other firms. In addition to supplying agricultural machinery to Bukhara, Italian firms planned to cooperate in land development. As a result of Soviet Interference and pressure from foreign trade organizations, the trade union in the BPSR трансCaucasus was terminated and partnerships ceased. For the first time, the material in the article is being debated.